Navigating Engagement: Exploring the Impact of Leadership, Work-Life Balance, and Job Satisfaction - Endayani, Fatmasari; Christania Putri, Katarina (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2024)
This study aims to examine the impact of leadership style, work-life balance, and job satisfaction on employee engagement in Perumda Tirta Kanjuruhan, Malang Regency. Utilizing a quantitative research approach, data were gathered through surveys distributed to employees of Perumda Tirta Kanjuruhan. The sample size was determined using the Slovin formula with a confidence level of 95%. Analysis was conducted employing multiple linear regression. Findings revealed significant effects of leadership style, work-life balance, and job satisfaction on employee engagement in Perumda Tirta Kanjuruhan, Malang Regency. Of the three independent variables, one variable, namely leadership style, had a positive but non-significant impact. This occurs due to several possible reasons. Firstly, the sample size might not have been large enough to detect a significant effect of leadership style on employee engagement. Additionally, the specific leadership styles observed within the organization may not have varied significantly, leading to limited variability in the data. Moreover, other unaccounted-for factors, such as organizational culture or external influences, could have overshadowed the impact of leadership style on employee engagement. Finally, measurement limitations or inaccuracies in assessing leadership style may have contributed to the non-significant findings.